Identitas dan Ideologi dalam Pembelajaran dan Pengajaran Bahasa Arab: Pendekatan Collaborative-Autoethnography - Fitria; Hattab, Muh.; Holis; Wargadinata, Wildana (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
This article aims to understand the identities and ideologies of learners and teachers of Arabic in Indonesia. This article highlights the importance of understanding identity and ideology in learning and teaching Arabic, including how individual and group identities affect language understanding, reception and usage. The data in this study was drawn from a dialogic and interactive process carried out through several media, such as GMeet, Whatsapp, and face-to-face, where we shared and discussed our educational backgrounds, interests in Arabic, activities we do outside of learning at school, and views on the ideal Arabic teacher. The results of this study found that the Arabic language became a symbol of love and a form of syiar rather than students and teachers. Not only because Arabic is considered an important language for religion, but also with Arabic, Islamic studies and identity can have a special place. The manifestation of love for the Arabic language can be embodied in the form of teaching. The recommendation for future research is to also consider the diversity aspect of autoethnographic data.